The post-2015 agenda: staying the course in maternal and child survival. (22nd January 2015) - Requejo, Jennifer Harris; Bhutta, Zulfiqar A
Abstract : In this article, we draw on available evidence from Countdown to 2015 and other sources to make the case for keeping women and children at the heart of the next development agenda that will replace the Millennium Development Goal (MDG) framework after 2015. We provide a status update on global progress in achieving MDGs 4 and 5, reduce child mortality and improve maternal health, respectively – showing that although considerable mortality reductions have been achieved, many more women's and children's lives can be saved every day through available, cost effective interventions. We describe key underlying determinants of poor maternal and child health outcomes and the need for well-coordinated, comprehensive approaches for addressing them such as introducing a combination of nutrition specific and sensitive interventions to reduce pervasive malnutrition, targeting interventions to the underserved to reduce inequities in access to care, and increasing women's social status through improved access to education and income-earning opportunities. In the wake of population momentum and emergencies such as the recent ebola outbreak and other humanitarian crises, health systems must be strengthened to be able to respond to these pressures. In conclusion, we underscore that the unfinished business of women's and children's health must be prioritized in the days ahead, and that ending preventable maternal and child deaths is not only a moral obligation but is achievable and essential to sustainable development moving forward.